Educational Content: Increasing Student Learning Motivation Through Instagram - Meliyana Hikmawati; Andriansyah; Pramudita Budi Rahayu (Communication Sciences Study Program, Universitas Islam Makassar, 2024)
This study aims to analyze the perception of SMAN 10 Makassar students on educational content published by the Instagram account @xavieraaputri, especially in increasing learning motivation. Along with the development of social media, especially Instagram, this platform plays a significant role in providing a positive influence through educational content from influencers. Xaviera Putri, an educational influencer, actively shares inspirational content, learning tips, and scholarship information that is relevant to students. The research method used is descriptive qualitative with in-depth interviews with 5-10 students who follow the @xavieraaputri account. Through this interview, the researcher explores students' perceptions regarding the influence of educational content on their learning motivation. The data obtained were analyzed to find patterns of student responses to the content and its impact on learning motivation. The results showed that the majority of students responded positively, felt more motivated, and were encouraged to improve their academic achievement after following the content. Thus, educational content from influencers on social media has significant potential in influencing students' learning motivation.